IFRS Convergence in Accounting Curriculum: How It is Perceived - Herdiani, A; ., Sunaryanto; ., Tuhardjo (KnE Social Sciences, 2018)
The purpose of this study is to examine the response of Intermediate Accounting lecturer to convergence of IFRS in accounting standards in Indonesia (PSAK). This response will affect the act of lecturers in adjusting the curriculum of Intermediate Accounting based on IFRS. The adjusted Intermediate Accounting curriculum will determine how the classroom teaching and learning will be carried out. Finally, students’ understanding will indicate how successful the process of learning has been held. This study examines the act of Intermediate Accounting lecturers at public universities in Malang that have vision and mission of accounting department in accordance with IFRS. The respondents are six intermediate accounting lecturers and students taking Intermediate Accounting subject. The result of this study is that currently Intermediate Accounting lecturers have a proper and sufficient knowledge of subject matter. Furthermore, they plan the lesson accordance with the needs and implement it in the classroom as well, so that the students get the right understanding as expected. Keywords: IFRS convergence, curriculum of intermediate accounting, teacher knowledge, teaching and learning process, students understanding